Reḍio Bāṃlādeśa kartrka pracācrita jātīẏa anushṭhāna ʻSukhī saṃsāra̕ o janasaṃkhyā niẏantraṇa bishaẏaka anyānya anushrhāna / bishaẏera mūlyāẏana - Khānama, Suphiẏā (Reḍio Bāṃlādeśa, 1978)
Evaluative study of the effectiveness of the Radio Bangladesh program Sukhī saṃsāra on population control and related subjects.